Evaluation of in vitro anti-Trypanosoma cruzi activity of medications benznidazole, amiodarone hydrochloride, and their combination - Angela Maria Lourenço; Cristiane Castro Faccini; Cristiane Aparecida de Jesus Costa; Gabrielle Balestrin Mendes; Abilio Augusto Fragata Filho (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract INTRODUCTION: Approximately seven to eight million people worldwide have Chagas disease. In Brazil, benznidazole is the most commonly used active drug against Trypanosoma cruzi; however, its efficacy is limited, and side effects are frequent. Recent studies suggest that amiodarone may be beneficial in the treatment of this disease, by exerting anti-T. cruzi action. This study evaluated changes in T. cruzi cell count in in vitro cultures subjected to different doses of benznidazole, amiodarone, and their combination. METHODS: T. cruzi (Y strain) cultures containing approximately 100,000 cells were treated with either 100mg, 50mg, 25mg, 12.5mg, or 10mg of benznidazole, amiodarone, or their combination. On the 4th day, cell count was compared to the baseline data. RESULTS: On the 4th day, no parasites were observed in any of the treated cultures. CONCLUSIONS: Benznidazole and amiodarone were equally effective in eliminating T. cruzi in culture. The combination of the two drugs was also equally effective, but our data cannot demonstrate synergism, as similar results were obtained when the drugs were tested individually or in combination. It is suggested that this study be repeated with other T. cruzi strains to determine whether similar results can be obtained again.